A critical review on blockchain assessment initiatives: A technology evolution viewpoint. Issue 11 (30th May 2020) - Colomo‐Palacios, Ricardo; Sánchez‐Gordón, Mary; Arias‐Aranda, Daniel
Abstract: Blockchain is considered as a major emerging technology that is having an ever‐increasing spread both in industrial and academic contexts. As the usage of blockchain keeps increasing, a fourth generation of blockchain platforms is being proposed. Thus, applications of blockchain have evolved towards wider scopes than cryptocurrency and asset management. In this context, it is important for practitioners to have deep understanding of various blockchain assessment initiatives. Therefore, this work discusses blockchain assessment initiatives from a technology evolution viewpoint. Furthermore, a mapping was conducted to identify factors that impact blockchain initiatives, synthesize available evidence, and identify gaps between relevant approaches available in the literature. As a result, nine selected works were analyzed based on applicability, research approach, assessment process, blockchain adoption process, and blockchain waves. The findings can help practitioners to understand the main assessment factors that undermine blockchain implementations.